2018
DOI: 10.1002/eat.22957
|View full text |Cite
|
Sign up to set email alerts
|

Self‐report measures of loss of control over eating: Psychometric properties in clinical and non‐clinical samples

Abstract: Objective Research evidence supports the clinical significance of subjective feelings of loss of control over eating; however, limited attention has been given to how this construct is assessed. Two measures have been developed in recent years (i.e., Eating Loss of Control Scale [ELOC] and Loss of Control over Eating Scale [LOCES]), but further validation in clinical and non‐clinical samples is needed. Method The current study evaluated the psychometric properties, including factor structure, criterion validit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 25 publications
(48 reference statements)
2
13
0
Order By: Relevance
“…Consistent with previous research, the BED group had elevated levels of self-reported impulsivity relative to HC in both food-specific and general measures of impulsivity ( Meule, 2013 ; Bodell et al, 2018 ). This increase in more general impulsivity is particularly interesting as it suggests that individuals with BED may experience challenges with behaviours beyond eating.…”
Section: Discussionsupporting
confidence: 87%
“…Consistent with previous research, the BED group had elevated levels of self-reported impulsivity relative to HC in both food-specific and general measures of impulsivity ( Meule, 2013 ; Bodell et al, 2018 ). This increase in more general impulsivity is particularly interesting as it suggests that individuals with BED may experience challenges with behaviours beyond eating.…”
Section: Discussionsupporting
confidence: 87%
“…Indeed, only 18.4% of the sample reported dietary restraint due to weight/shape concerns. Mean global EDE-Q scores for the sample were below clinical cutoffs (Mond et al, 2004;Schaefer et al, 2018), yet LOCES scores were consistent with published means from nonclinical samples (Bodell et al, 2018).…”
Section: Discussionsupporting
confidence: 79%
“…Of note, previous studies have suggested that subjective binge episodes are clinically meaningful, but have low reliability [ 25 27 ]. Improved diagnostic guidelines, assessment tool instructions, and new measures (e.g., the Eating Loss of Control Scale and the Loss of Control over Eating Scale) may help increase reliability and improve diagnosis and severity assessment across disorders characterized by binge eating [ 10 , 11 , 28 , 29 ]. Our findings could help inform the refinement of these assessment tools to measure LOC.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings could help inform the refinement of these assessment tools to measure LOC. For example, although eating disorder experts who contributed to the development of the Loss of Control over Eating Scale (LOCES [ 11 ];) highly rated items describing mindless eating as “covering or reflecting” LOC, these mindless eating items had lower corrected item-total correlations [ 11 ], and one study found that the LOCES-Brief, which excludes these mindless eating items, provided a better fit to data from both clinical and non-clinical samples [ 28 ]. The current results more explicitly suggest that conflation of mindless and LOC eating may be a common cause of binge eating misdiagnosis.…”
Section: Discussionmentioning
confidence: 99%